2023
DOI: 10.1186/s13071-023-05738-9
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of long noncoding RNA (lncRNA) and messenger RNA (mRNA) expression in the liver of Beagle dogs by Toxocara canis infection

Abstract: Background Long non-coding RNAs (lncRNAs) and messenger RNAs (mRNAs) play crucial roles in regulating various physiological and pathological processes. However, the role of lncRNAs and mRNAs in mediating the liver response during Toxocara canis infection remains incompletely understood. Methods In the present study, the expression profile of lncRNAs and mRNAs was investigated in the liver of Beagle dogs infected by T. canis using high-throughput RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Recent studies ( 3 - 5 ) have shown that lncRNAs play an important role in cardiovascular diseases, including ICM. Moreover, studies ( 6 - 8 ) have found that lncRNAs can act as competing endogenous RNAs (ceRNAs) and regulate the expression of messenger RNA (mRNA) by competing with mRNA for microRNAs (miRNAs).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies ( 3 - 5 ) have shown that lncRNAs play an important role in cardiovascular diseases, including ICM. Moreover, studies ( 6 - 8 ) have found that lncRNAs can act as competing endogenous RNAs (ceRNAs) and regulate the expression of messenger RNA (mRNA) by competing with mRNA for microRNAs (miRNAs).…”
Section: Introductionmentioning
confidence: 99%